The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0103-335220182601
|View full text |Cite
|
Sign up to set email alerts
|

Eleições como de costume? Uma análise longitudinal das mudanças provocadas nas campanhas eleitorais brasileiras pelas tecnologias digitais (1998-2016)

Abstract: Resumo: O objetivo deste artigo é empreender um estudo das principais inovações ocorridas nas e-campanhas brasileiras desde 1998. Como método de análise realizamos uma sistematização dos principais achados efetuados pela literatura sobre inovações nas e-campanhas brasileiras e apresentamos dados sobre o uso das mídias sociais e da internet pelos candidatos nas campanhas eleitorais no Brasil desde 2006, quando estes passaram a ser reunidos de maneira mais sistemática. Concentraremos nosso exame nas eleições par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
0
5
0
8
Order By: Relevance
“…Hypermedia campaigns are developed with digital media and occur through advertisements distributed via network, for a selected audience that not only consumes but also produces and disseminates political content (Howard, 2006;Ituassu et al, 2018). In Brazil, Braga and Carlomagno (2018) reiterate the political use of social networks and attest to their greater intensity during the last election campaigns. The survey released by Datafolha in the 2018 presidential elections showed that 68% of voters have access to some social network (Facebook, Instagram, Twitter, Whatsapp, etc.…”
Section: Explore Importance Of the Problemmentioning
confidence: 96%
See 1 more Smart Citation
“…Hypermedia campaigns are developed with digital media and occur through advertisements distributed via network, for a selected audience that not only consumes but also produces and disseminates political content (Howard, 2006;Ituassu et al, 2018). In Brazil, Braga and Carlomagno (2018) reiterate the political use of social networks and attest to their greater intensity during the last election campaigns. The survey released by Datafolha in the 2018 presidential elections showed that 68% of voters have access to some social network (Facebook, Instagram, Twitter, Whatsapp, etc.…”
Section: Explore Importance Of the Problemmentioning
confidence: 96%
“…12.034/09, the use of digital tools during the campaigns, making way to the consolidation of a new communication channel between parties, candidates and voters. But it was in the 2014, 2016 and 2018 elections that the exaggerated use of the internet and social media was detected as an instrument of propaganda by candidates (Braga and Carlomagno, 2018). In 2018 elections, Law 9,504/97, issued by National Congress in 2017, allowed paid posts to be showed on Facebook and Instagram platforms (content boosting), event that expanded the reach of campaigns carried out on digital social networks.…”
Section: Explore Importance Of the Problemmentioning
confidence: 99%
“…No Brasil, a literatura vem apontando a emergência de um novo paradigma comunicacional-eleitoral com presença imprescindível das tecnologias de comunicação. As eleições 2016 consolidaram essa tendência, com os candidatos utilizando alguma mídia digital para interação (Braga;Carlomagno, 2018, p. 7). A nossa hipótese é que, nos municípios em que determinados recursos são limitados, as campanhas mesclam redes e rua -"the old style of campaigning" (Farrell, 2009): intensivas, com candidatos, filiados e voluntários desenvolvendo todo ou parte do trabalho, envolvendo a interação com eleitores.…”
Section: Profissionalização E Campanhas Nos Municípiosunclassified
“…Nesse contexto, na última década, os estudos sobre campanha eleitoral passaram a tratar com mais destaque os ambientes online de propaganda. Na agenda das campanhas online, os estudos se deslocam com rapidez, passando por websites, blogs, Wikipedia, Orkut, Twitter, Facebook, chegando mais recentemente ao Instagram e ao What-sApp Figueiredo, 2007;Carlomagno, 2018;Santos, 2017a;Chaia, 2007;Coutinho;Safatle, 2009;Ituassu et al, 2019;Lifschitz, 2015;Murta et al, 2017;Penteado;Fiacadori, 2016). Os websites, embora tenham aparecido como objeto importante ao longo da primeira década do século XXI, e ainda que sirvam de repositório de conteúdos, perderam espaço para as redes sociais, que rapidamente ganharam atenção nas pesquisas, especialmente após o "fenômeno Obama".…”
Section: Campanha E Propaganda Eleitoral Nas Eleições Brasileirasunclassified